The impact of Benson's relaxation technique on the quality of life of operating room nurses in hospitals southwest Iran: a randomized controlled trial - Zinat Mohebbi; Sina Ghanbarzadeh; Alireza Ejraei; Somayeh Gheysari; Fahimeh Alsadat Hosseini (BMC, 2024)
Abstract Background In clinical settings, continuous changes lead to increased professional stress, affecting the quality of life of nurses. Some complementary interventions may influence the improvement of the quality of life. This study aimed to determine the effect of Benson's relaxation technique on the operating room nurses' quality of life. Methods In this clinical trial, 180 operating room nurses were randomly allocated to two groups: intervention (Benson's relaxation technique) and control (routine activity). The study was conducted from December 2021 to March 2022 in hospitals affiliated with Shiraz University of Medical Sciences. Benson's relaxation technique was performed twice daily by the intervention group for 8 weeks. Quality of life was measured before and after the intervention using the SF-36 questionnaire. Data were analyzed using SPSS version 21 software, with a significance level set at a P < 0.05. Results After the intervention, the results showed that Benson's relaxation technique led to an increase in the quality of life in the intervention group (P < 0.0001). In terms of quality-of-life dimensions, significant improvements were observed in the intervention group in the domains of physical problems (P < 0.05), emotional problems (P < 0.05), general health (P < 0.05), pain (P < 0.0001), and social functioning (P < 0.05). However, no significant differences were found in the dimensions of physical functioning, energy, and emotional well-being. Conclusions Benson's relaxation technique can serve as a complementary method to improve various dimensions of the operating room nurses' quality of life. Trial Registration Number IRCT20211002052650N1 with the Clinical Trial Registry (26.10.2022).